Analysis of Dialysate pH and Temperature Stability on Hemodialysis Machines Using Internet of Thing Technology - Noviyanto Putera P; Lusiana Lusiana; Endang Dian Setioningsih; Sari Luthfiyah; Abhilash Pati (Indonesian Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2023)
Therapy for kidney replacement with hemodialysis is a treatment that is carried out in patients with Chronic Kidney Failure to survive. The purpose of this study was to determine the stability of the dialysate fluid in the hemodialysis machine by measuring the temperature using the DS18B20 sensor and measuring the dialysate pH using the 4502C sensor on pre and post-hemodialysis. The research method and the manufacture of this module use a pre-experimental research design with the type of research "one group posttest design" the independent variables are the pH value and Dialysate Temperature, the dependent variable is the pH and Temperature Sensor, the control variable is the Traceable Tool. This research made a module using an Esp32 microcontroller system with an LCD that can be monitored with Android via the Internet of Things (IoT) system. 03 and the comparison of the results of the dialysate temperature values ​​at the time of pre and post-obtained the maximum measurement error of 0.2%. From the measurement and analysis data, it can be concluded that there is no effect of pH and temperature values ​​during pre and post hemodialysis.